The effect of teacher characteristics on students' science achievement - Pietro Sancassani (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Using data from TIMSS 2015, an international large-scale assessment of student skills, I investigate the effect of teacher characteristics on students' science achievement. My identification strategy exploits the feature that in many education systems different science domains (physics, biology, chemistry, and earth science) are taught by different teachers. The availability of students' test scores as well as teachers' questionnaires for each of these domains allows me to implement a withinstudent approach which controls for unobserved student heterogeneity. I find a positive and significant effect of teacher specialization in the specific science domain on students' results, equivalent to 1.7% of a standard deviation. Holding a Master's degree, pedagogical preparation and teaching experience have no significant effect. Teachers' experience has a negative impact on the extent to which students like to study a subject or find teaching engaging.
Keywords: I21; I29; C21; J24; 330; Teachers; student achievement; teacher characteristics; education production function; TIMSS